Participation of customers on the co-creation of service climate in the hotel industry : a case study of Frogner House Hotel Norum - Shrestha, Arjun Kumar (Universitetet i Nordland, 2014)
Masteroppgave i bedriftsøkonomi - Universitetet i Nordland, 2014